If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + -4(5x + y)) = 0 4(5x + (5x * -4 + y * -4)) = 0 4(5x + (-20x + -4y)) = 0 Combine like terms: 5x + -20x = -15x 4(-15x + -4y) = 0 (-15x * 4 + -4y * 4) = 0 (-60x + -16y) = 0 Solving -60x + -16y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16y' to each side of the equation. -60x + -16y + 16y = 0 + 16y Combine like terms: -16y + 16y = 0 -60x + 0 = 0 + 16y -60x = 0 + 16y Remove the zero: -60x = 16y Divide each side by '-60'. x = -0.2666666667y Simplifying x = -0.2666666667y
| Y=2.3x+0.2 | | 171=3x+2x^2 | | -21-18y+y=13 | | e^4x+2e^2x-24=0 | | 1000*q=1.4597 | | log81^1/9=x | | 3*-7-6y+y=13 | | 12p-15+6p=-27 | | 18x=x+y | | 0=-2x^2-10x | | Y=-0.3x-5.3 | | 2x^2+2x+25=289 | | 3ab-ab+b= | | 96+.18x+.20x=376 | | 6/x^2 | | 3(-7-6y)-y=13 | | 6x+10=35-9x | | 18-x+x+14-x+5=36 | | 2x^2-31x-475=0 | | 5/6x-4/5=0 | | x=3(13/6)-9 | | 2x-10+3x-5=90 | | 2x^2-30x-475=0 | | 7=x^2-32 | | 2(19-3y)=10 | | 4-(7x-3)=5 | | 2d+5=20-3e | | (42)(6)=(x)(32-x) | | x-8.1=5.33 | | 4x+6=-54-6 | | -2/3x-5=-1 | | P=pw |